Інтелектуальний потенціал територіальних громад Вижницького району Чернівецької області як основа їх інноваційного розвитку - Костащук Іван; Kostashchuk Ivan; Миронюк Станіслав; Myroniuk Stanislav (Видавничий дім «Гельветика», 2025)
Резюме. Актуальність дослідження полягає в тому, що нині Україна переживає важкий етап свого становлення через багаторічну економічну кризу, пандемію Covid-19, а також війну з рф, яка спричинила багато руйнувань міських та сільських поселень, замінувань територій, розпочатий процес децентралізації та багато інших проблем як економічного, так і соціального характеру. Інтелектуальний потенціал (капітал) повинен стати запорукою успішного післявоєнного становлення. Саме в цей час в Україні буде потрібно залучення до різних сфер висококваліфікованих працівників різних професій на всіх адміністративно-територіальних рівнях – територіальних громадах, районах, регіонах, областях та національному (загальнодержавному) рівні.Предметом дослідження є аналіз територіально-просторових особливостей формування інтелектуального потенціалу територіальних громад Вижницького району, який вирізняється своєю природною, економічною, соціокультурною, транспортно-логістичною унікальністю. Для дослідження вибрано учнівську молодь, яка в недалекому майбутньому буде основною рушійною силою змін у післявоєнному відновленні громад і територій усіх регіонів України. Метою роботипередбачено детальний аналіз територіально-просторових відмін у формуванні інтелектуального потенціалу громад вибраного району за результатами ЗНО 2021 року, НМТ 2024 року (за трьома навчальними дисциплінами: українська мова, математика та історія України), ІІІ етапу Всеукраїнських учнівських олімпіад та ІІ етапу конкурсу-захисту науково-дослідницьких робіт учнів-членів МАН України у 2024–2025 навчальному році (усі дисципліни).В основі методології дослідження лежить комплексно-географічний підхід із використанням статистичного методу, а також ранжування за рейтинговими показниками рівня розвитку інтелектуального потенціалу учнівської молоді в територіальних громадах Вижницького району. Також використовувалисяпорівняльно-географічний аналіз і синтез, математичне оброблення статистичних даних та інші.Результати роботимають теоретичне та практичне значення, яке простежується у виявленні різних чинників на процес формування інтелектуального потенціалу (капіталу) в окремих громадах Вижницького району. Сфера застосування результатів: одержані дані можуть бути використаними в розробленні Стратегій та Програм соціально-економічного розвитку Вижницького району та окремих його громад, управліннями освіти з метою покращення рівня освіти та збільшення зацікавленості учнів до олімпіад та конкурсів, управліннями регіонального розвитку (чи іншими, які за це відповідають у громадах) з метою оптимального планування розвитку освітньої мережі та покращення транспортної доступності до ЗЗСО. Висновки: інтелектуальний потенціал громад Вижницького району сформувався під впливом різних чинників, які впливають на освітній процес в ЗЗСО. Простежено, що не завжди в гірських районах визначальними є природні умови, як-от Путильська громада за результатами тестування та олімпіад є лідером в районі. Громади району мають різні рівні інтелектуального розвитку серед учнівської молоді.Перспективи подальших досліджень полягають у більш детальному вивченні інтелектуальних здібностей різних вікових груп населення територіальних громад району, пошуку шляхів підвищення рівня освіти як шкільної, так і освіти дорослих.

Abstract. The relevance of the study is that today Ukraine is going through a difficult stage of its formation due to the long-term economic crisis, the Covid-19 pandemic, as well as the war with the Russian Federation, which caused a lot of destruction of urban and rural settlements, undermining of territories, touched the initiated process of decentralization and many other problems of both economic and social nature. Intellectual potential (capital) should become the key to successful post-war formation. It is at this time that Ukraine will need to attract highly qualified workers of various professions to various fields at all administrative and territorial levels – territorial communities, raions, regions, oblasts and the national (state) level. The subject of the study is the analysis of the territorial and spatial features of the formation of the intellectual potential of territorial communities of Vyzhnytsia raion, which is distinguished by its natural, economic, socio-cultural, transport and logistical uniqueness. The study selected students, who in the near future will be the main driving force of change in the post-war reconstruction of communities and territories of all regions of Ukraine. The purpose of the work was to provide a detailed analysis of territorial and spatial differences in the formation of the intellectual potential of communities in the selected raion based on the results of the 2021 external independent evaluation, the 2024 national multi-subject test (in three academic disciplines: Ukrainian language, mathematics, and history of Ukraine), the 3rd stage of the All-Ukrainian Student Olympiads, and the 2nd stage of the competition-defense of research works by students-members of the Academy of Sciences of Ukraine in the 2024–2025 academic year (all disciplines). The research methodology is based on a comprehensive geographical approach using statistical methods, as well as ranking by rating indicators of the level of development of the intellectual potential of students in the territorial communities of Vyzhnytsia raion. Comparative geographical analysis and synthesis, mathematical processing of statistical data, and others were also used. The results of the work have theoretical and practical significance, which is traced in the identification of various factors in the process of forming intellectual potential (capital) in individual communities of Vyzhnytsia raion. Scope of application of the results: the data obtained can be used in the development of Strategies and Programs for the socio-economic development of Vyzhnytsia raion and its individual communities, by education departments in order to improve the level of education and increase students’ interest in olympiads and competitions, by the departments of regional development (or others responsible for this in communities) in order to optimally plan the development of the educational network and improve transport accessibility to the general secondary education institutions. Conclusions: the intellectual potential of the communities of Vyzhnytsia raion was formed under the influence of various factors that affect the educational process in the general secondary education institutions. It was observed that natural conditions are not always decisive in mountainous areas, since Putyla community is a leader in the raion according to the results of testing and olympiads. The communities of the raion have different levels of intellectual development among students. The prospects for further research are in a more detailed study intellectual abilities of different age groups of the population territorial communities raion, and in finding ways to improve the level education, both school and adult education.
Intellectual potential of territorial communities of Vyzhnytsia raion of Chernivtsi oblast as the basis of their innovative development
Весь випуск: https://journals.kmf.uzhgorod.ua/index.php/geograph/issue/view/7
Keywords: інтелектуальний потенціал; ЗНО; НМТ; рівень освіти; освітня мережа